Pengaruh Model Problem Based Learning terhadap Keterampilan Menulis Teks Deskripsi Siswa Kelas VII SMP Negeri 14 Sijunjung - Muhammad Nur Sulaiman Eato; Ena Noveria (Lembaga Yasin AlSys, 2025)
The low level of descriptive text writing skills among Grade VII students at SMP Negeri 14 Sijunjung is marked by difficulties in developing ideas, selecting appropriate vocabulary, and constructing well-structured sentences. To address these issues, this study aims to analyze the effect of the Problem Based Learning (PBL) model on students’ descriptive writing skills. A quantitative approach was employed using a quasi-experimental method with a One Group Pretest-Posttest design. The population consisted of 57 students, with the sample drawn from Class VII B. Data were collected through a performance-based descriptive text writing test and analyzed using a t-test. The results revealed a significant improvement in writing skills following the implementation of the PBL model, as indicated by an increase in the average score from the